Digital photos from concept to completion learn by video. - Grey, Tim.; Safari eBooks ([S.l.] : Peachpit Press, 2011)
"This innovative product uses interactive video to walk through the process of creating beautiful photos with a variety of subjects - including landscapes, macro photos, panoramas, HDR, and more. The lessons take the viewer along as instructor Tim Grey starts with the subject and an idea, evaluates shooting conditions and plans his shot, configures his camera and captures the image, and then optimizes the image with software for a polished final result. Viewers will gain a better sense of how to think about images, how to approach their capture and optimization, and how to achieve a distinctive photographic vision. Featuring a blend of on-location live footage and software-based instruction, this title should change the way viewers take their photos."--Resource description page.
Title and publication information from resource description page (viewed 3/7/12).
"Video2brain.com"--Video screen
Presenter, Tim Grey.
Keywords: Photography -- Digital techniques; Image processing -- Digital techniques; Electronic books